Non Invasive Diagnostic Techniques in Clinical Dermatology - Berardesca, Enzo.; Maibach, Howard I.; Wilhelm, Klaus-Peter.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book is a comprehensive but compact guide to the latest technical and technological developments in the growing field of non invasive diagnosis in clinical dermatology. Information is provided on the practical and technical characteristics of a wide range of equipment and methods for in vivo measurements that aid in the investigation of skin function, the evaluation of topically applied products, and the monitoring of skin disease. Individual sections are devoted to imaging techniques, skin analysis, superficial skin analysis, skin mechanics, water and stratum corneum hydration, and erythema and blood flow. All of the authors are experts in the field, with detailed knowledge of the techniques they describe. Non Invasive Diagnostic Techniques in Clinical Dermatology will be of value for all dermatologists, whether they are engaged in delivering patient care or in research programs, for cosmetic scientists, and for biologists involved in skin research and product assessment.
Imaging Techniques -- Skin Analysis -- Superficial skin Analysis -- Water and Stratum Corneum Hydration -- Erythema and Blood Flow -- Hair and Follicles -- Nails.
Keywords: Medicine; Human physiology; Dermatology; Cytology -- Research_xMethodology.; Medicine & Public Health; Dermatology; Biological Techniques; Human Physiology